2020
DOI: 10.12788/jhm.3373
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Pediatric Hospital Medicine: Challenges and Opportunities

Abstract: P ediatric hospital medicine (PHM) is in the midst of an exciting period of growth. In 2016, the American Board of Medical Specialties approved the petition for PHM to become the newest pediatric subspecialty, taking PHM on a divergent path from the Focused Practice in Hospital Medicine designation established for adult hospitalists. Establishment as a subspecialty has allowed PHM to defi ne the unique skills and qualifi cations that hospitalists bring to patients and the healthcare system. These skills and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…2,3 PHM fellowships, the first 3 of which were initiated in the United States in 2003, were developed in response to the growing complexity of hospitalized children and the knowledge that hospitalists play a key role in medical education, quality improvement (QI), care coordination, health informatics, scholarly activity, and more, much of which is not formally taught in residency. [4][5][6] The American Board of Pediatrics approved subspecialty status for PHM in December 2015, and the American Board of Medical Specialties later approved it in October 2016. There are now .30 PHM fellowship programs accredited by the Accreditation Council for Graduate Medical Education (ACGME) and .60 total programs in existence.…”
mentioning
confidence: 99%
“…2,3 PHM fellowships, the first 3 of which were initiated in the United States in 2003, were developed in response to the growing complexity of hospitalized children and the knowledge that hospitalists play a key role in medical education, quality improvement (QI), care coordination, health informatics, scholarly activity, and more, much of which is not formally taught in residency. [4][5][6] The American Board of Pediatrics approved subspecialty status for PHM in December 2015, and the American Board of Medical Specialties later approved it in October 2016. There are now .30 PHM fellowship programs accredited by the Accreditation Council for Graduate Medical Education (ACGME) and .60 total programs in existence.…”
mentioning
confidence: 99%
“…13 Both academic practice and good mentorship may correlate with increased PF among PHM physicians, while high weekend, overnight, and in-house clinical effort may threaten workforce sustainability. 9,13,14 Interventions to promote PHM PF may be most effective when tailored to these concepts. The objective of this study was to describe how PHM physicians at our institution conceptualize PF.…”
Section: Introductionmentioning
confidence: 99%
“…The state of PHM PF is not well understood, though limited studies have reported high job satisfaction overall 13 . Both academic practice and good mentorship may correlate with increased PF among PHM physicians, while high weekend, overnight, and in‐house clinical effort may threaten workforce sustainability 9,13,14 . Interventions to promote PHM PF may be most effective when tailored to these concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Many contended that residency training alone was already producing clinicians who meet the American Academy of Pediatrics definition of a pediatric hospitalist—that is, pediatricians working in the hospital providing care in multiple care settings (pediatric ward, labor and delivery, newborn nursery, emergency department, neonatal, and/or pediatric intensive care units) 1 . However, as core competencies for PHM practice were delineated, there was a growing recognition that the children being cared for in the inpatient setting were increasingly complex 2 . There was also the recognition that, to provide the best clinical care, pediatric hospitalists were ideally suited to lead system‐level efforts that would directly translate to enhanced quality of care delivery for children 2 .…”
mentioning
confidence: 99%
“…However, as core competencies for PHM practice were delineated, there was a growing recognition that the children being cared for in the inpatient setting were increasingly complex 2 . There was also the recognition that, to provide the best clinical care, pediatric hospitalists were ideally suited to lead system‐level efforts that would directly translate to enhanced quality of care delivery for children 2 . It became clear that additional training would provide incremental benefit for a growing and complex field.…”
mentioning
confidence: 99%